Pickleball and mental health in adults: A systematic review - Cerezuela, Juan-Leandro; Lirola, Maria-Jesus; Cangas, Adolfo J. (Frontiers in Psychology, 2023)
Physical activity has been extensively studied and numerous mental health benefits have been found. Pickleball is an emerging racquet sport, which is characterized by its accessibility to all audiences and has become especially popular in the United States among the elderly. It is a novel team game and its inclusive nature is innovative for health improvement. The purpose of this systematic review was to review and evaluate existing studies that have examined the effects of pickleball on the mental and psychological health of individuals. A systematic review was conducted on articles found in Scopus, PubMed, Elsevier, Web of Science, PsyINFO, Dialnet and EBESCO from 1975 to the present. The keywords used was a five combination between "Pickleball” joint with different terms by the connector AND, the second part of the combo could be "mental disorder" OR "anxiety" OR "depression" OR "psychological health" OR "mental health". Eligibility criteria included: papers focused on pickleball, in English or Spanish, on mental health variables, without establishing an age range. We excluded duplicate works, without access or that did not address the objective of this study. The search resulted in 63 papers, of which 13 were selected. 90.74% of the population were people over 50 years of age. The results show significant improvements in the different psychological variables measured in pickleball practitioners: personal well-being, life satisfaction, depression, stress, happiness, etc. Pickleball shows potential as a new tool to work and improve people's mental health. We found an inclusive sport that does not need adaptations, resulting of great interest to be worked in different populations with mental problems.